Computational particle fluid dynamics simulation of gas–solid flow in a 3 MWth dual-circulation fluidized bed for chemical looping process - Yankun Li; Tuo Guo; Xintong Guo; Xiude Hu; Qingjie Guo; Shengzhong He; Zimiao Zhou (Carbon Resources Conversion, 2024)
Regulation of gas–solid flow is crucial for optimizing the operation efficiency of dual-circulating fluidized beds that are considered to be the most appropriate type of chemical-looping reactors. Herein, a computational particle fluid dynamics method was employed to simulate the gas–solid flow in a 3-MWth dual-circulating fluidized bed used for chemical-looping combustion and gasification. The influence of structural difference between units on particle residence time was determined. The multi-parameter control mechanism of pressure, particle circulation, and particle residence time in a whole-loop system was investigated. Results revealed that under stable particle circulation, the particle residence time in the fuel reactor is much longer than that in the air reactor. The axial forces on the particles are reduced upon increasing particle density and size, leading to particle accumulation in the dense-phase zone. When the particle properties are stable, increasing the fluidizing gas flow rates by the same proportion leads to identical pressure drops on the involved two loop seals, which cause symmetrical alterations in the particle circulation rate between the air and fuel reactors. The dual-circulating fluidized bed exhibits certain multi-condition adaptability, which is limited by the stock bin volume. Overall, this study is beneficial for effective and economical optimization of the operation of chemical-looping dual-circulating fluidized beds.